Integrating Problem-Based Learning with Artificial Intelligence: Transforming Student-Centered Education in the Digital Era - Novak , Luka; Kovač, Ana; Zupančič, Luka (International Journal of Educational Technology and Artificial Intelligence, 2025)
This article explores the integration of Problem-Based Learning (PBL) and Artificial Intelligence (AI) to create an innovative, student-centered educational model. In an era where critical thinking, creativity, and digital literacy are essential, combining PBL—a constructivist approach to learning—with AI technologies can enhance personalization, collaboration, and problem-solving in real-world contexts. The paper discusses the theoretical underpinnings of PBL and AI, identifies the pedagogical benefits of their synergy, and presents models for implementation in higher education. A case study approach is used to illustrate practical applications, followed by a discussion of challenges, ethical considerations, and future directions. This case study demonstrates the effectiveness of integrating problem-based learning (PBL) with artificial intelligence (AI) in a university-level environmental engineering course. By engaging students in a real-world challenge—designing a sustainable water system for a drought-prone region in Slovenia—the study revealed how AI-supported simulations and data-driven decision-making can deepen understanding of complex environmental issues. Students utilized AI tools to access region-specific data, simulate multiple climate scenarios, and evaluate the feasibility and resilience of solutions such as rainwater harvesting and retention ponds.